Non-surgical facial aesthetics: Should this be incorporated into medical education? - Umar Rehman; Frances Amy Johanna Freer; Mohammad Sohaib Sarwar; Sukhpreet Singh Dubb; Peter A. Brennan (Elsevier, 2022)
Background: Non-Surgical Facial Aesthetics (NSFA) encompasses a range of minimally invasive procedures. Complications associated with NSFA often present to local Emergency Departments. There is no representation of NSFA in the undergraduate curriculum. Medical students appear to have little to no exposure to NSFA during their training.The main aims of this study were to gain an insight into the views of final year medical students in pursuing a career in NSFA and assessing their understanding of NSFA competence and complications of common procedures. Method: ology: An online survey was completed by 148 medical students across two English Universities. 106/148 (71.6%) of students were from University A and 42/148 (28.4%) were from University B. Results: 47.6% (70/148) of medical students would consider pursuing a career in NSFA after graduating from medical school. 76.3% (87/148) and 80.7% (92/148) of students were not aware of the complications associated with the administration of dermal fillers and Botox injections respectively. Most medical students felt a single day training program in NSFA was sufficient to administer non-surgical rhinoplasty 67.8% (99/148) dermal fillers 67.1% (98/148) and Botox injections 68.5% (100/148). Conclusion: Despite a large proportion of medical students considering a career in NSFA the majority were unaware of the common complications. Incorporation of NSFA into undergraduate curriculum should improve enhance patient safety, effective management of complications and augment future learning and career progression. This may be achieved by through signposting, student-selected components and as part of structured head and neck teaching.